GUIDE FOR QUALITY ASSURANCE IN VOCATIONAL EDUCATION AND TRAINING FOR TOURISM - IRIMIEA, Silvia; ȘERBAN, Adriana (2014)
The project Towards a common recognition of quality assurance systems in VET for Tourism (QualVET) has been undertaken by the Centre for Tourism Training (Babeş-Bolyai University) as a coordinating partner for the purpose of carrying through the quality assurance reform in VET (Vocational Education and Training) for tourism, a reform that the institution has committed itself to implement. Quality assurance has become a major concern of training providers in Romania, since VET has acquired a greater prominence as a training alternative to academic training. It is also thought that such a significant process must involve the Romanian vocational training provider in an international exchange of expertise and experience which can enhance a better understanding of quality assurance in general and the mechanisms used in other countries.